APLIKASI NEUROMUSCULAR TAPING PADA KONDISI CARPAL TUNNEL SYNDROM UNTUK MENGURANGI NYERI - Ismaningsih Ismaningsih; Ayu Permata (Jurnal Ilmiah Fisioterapi, 2020)
Background: Carpal tunnel syndrome (CTS) is a collection of symptoms and signs of disease caused by squeezing of the median nerve in the carpal tunnel in the wrist. This CTS condition is one of the most common types of neuropathy. This syndrome arises with symptoms of pain, numbness, and weakness in the hands due to compression of the median nerve. Carpal tunnel syndrome is a syndrome associated with repetitive motion and a fixed position for a long duration so that it affects the blood supply to the hands and causes pain. Objective: This research is aimed at sufferers of Carpal Tunnel Syndrome condition to reduce pain. Physiotherapy interventions given in CTS conditions, namely pain reduction that can be done with various actions including by providing Neuromuscular Taping technique. Research Method: Case study with pre and post test research design that compares the level of pain values ​​before and after which is measured by measuring instruments Visual Analogue Scale (VAS) for the administration of Neuromuscular Taping intervention in the condition of carpal tunnel syndrome for 3 weeks. Results: Analysis of the different values ​​of pain tests with VAS in the sample group with a significance value of 0.006 which shows <0.05 which means there is an influence of giving Neruromusculer taping to changes in the VAS pain level in patients with Carpal Tunnel Syndrome.